Comparative Study of the Lipase Enzyme Extracted From the Bacterial Isolates in Lipid Enriched Soil of Kathmandu Valley in Nepal - Yadav, Nishu (International Journal of Pharmaceutical & Biological Archive, 2013)
Comparative Study of the Lipase Enzyme Extracted From the Bacterial Isolates in Lipid Enriched Soil of Kathmandu Valley in Nepal